2010
DOI: 10.1038/ajg.2009.687
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Mortality in Non-Variceal Upper Gastrointestinal Bleeders: Validation of the Italian PNED Score and Prospective Comparison With the Rockall Score

Abstract: The Italian 10-point score for the prediction of death was successfully validated in this independent population of patients with non-variceal gastrointestinal bleeding. The PNED score is accurate and superior to the Rockall score. Further external validation at the international level is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 23 publications
6
114
0
1
Order By: Relevance
“…The number of comorbidities was significantly higher in patients who died and it was an independent predictor of death (OR: 1.6; 95% CI: 1-2.5, p = 0.045). This finding is similar to that observed in other studies, particularly RUGBE and PNED studies (3,5,8). On the other hand, hypovolemic shock as cause of death was significantly higher in patients without comorbidities than in those with comorbidities (48 vs. 21%, p = 0.02).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The number of comorbidities was significantly higher in patients who died and it was an independent predictor of death (OR: 1.6; 95% CI: 1-2.5, p = 0.045). This finding is similar to that observed in other studies, particularly RUGBE and PNED studies (3,5,8). On the other hand, hypovolemic shock as cause of death was significantly higher in patients without comorbidities than in those with comorbidities (48 vs. 21%, p = 0.02).…”
Section: Discussionsupporting
confidence: 80%
“…Current evidence sug- gests that early administration of PPIs is the standard treatment of patients with NVUGB (20)(21)(22)(23)(24). The rebleeding rate observed in our patients (3.4%) was similar to that observed in the Italian PNED study (3.2%) and in other recent publications (17,18), but it was significantly lower than that reported in the Canadian RUGBE study (14.1%) (3,5,8). The divergence of our results from the ones of the Canadian study may be explained because a higher proportion of our patients received combined endoscopic therapy (adrenaline injection plus BICAP) than in the Canadian study; combined therapy has been shown to be superior to pharmacologic treatment for reduction of rebleeding in controlled trials (25)(26)(27).…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…An Italian score of 10, the PNED score [21] , was developed and validated to predict 30 d mortality after non-variceal bleeding. The PNED score is based on ten variables, (8 clinical and 2 laboratorial), and ranges from 0 to 24 (Table 4).…”
Section: Clinical and Endoscopic Scoresmentioning
confidence: 99%